1991
DOI: 10.1007/bf00157745
|View full text |Cite
|
Sign up to set email alerts
|

The possible influence of sea level rise on the precarious dunes of Devesa del Saler Beach, Valencia, Spain

Abstract: The Saler Beach dune field in Spain was partially destroyed between 1970 and 1973 due to building development. Presently great efforts to restore some dunes has begun. The possible consequence of a sea level rise for the Saler dune field is discussed according to different scenarios.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Plantings of E. maritimum on a sandy shingle beach in Sizewell, Suffolk, Britain, during April/May have shown that planting location on the beach/dune profile is the most important factor that affected establishment; neither organic matter nor fertilizer had significant effects (Walmsley & Davy 1997cWalmsley 2002). Eryngium maritimum has also been reestablished in dunes by plantings in Spain (Sanjaume & Pardo 1991;Escaray et al 2010;Ley Vega de Seoane 2010). Young plants can be grown from root fragments (about 6 cm long) from the main root, as well as from offshoots from nursery plants.…”
Section: Restoration Measuresmentioning
confidence: 99%
“…Plantings of E. maritimum on a sandy shingle beach in Sizewell, Suffolk, Britain, during April/May have shown that planting location on the beach/dune profile is the most important factor that affected establishment; neither organic matter nor fertilizer had significant effects (Walmsley & Davy 1997cWalmsley 2002). Eryngium maritimum has also been reestablished in dunes by plantings in Spain (Sanjaume & Pardo 1991;Escaray et al 2010;Ley Vega de Seoane 2010). Young plants can be grown from root fragments (about 6 cm long) from the main root, as well as from offshoots from nursery plants.…”
Section: Restoration Measuresmentioning
confidence: 99%
“…However, inland areas are less suitable because of higher vegetation cover [31] , [65] . This constraint on the width of suitable breeding habitat is particularly relevant for the conservation of breeding populations of Kentish Plover, especially under the current context of coastal regression [66] , and under future scenarios of sea-level rise from climate change [67] , [68] . Therefore, the protection of the widest beaches would be an adequate strategy for plover conservation, given the difficulty of mitigating the effects of coastal erosion.…”
Section: Discussionmentioning
confidence: 99%